Figurative Language Found on Joe Biden’s Victory Speech in Wilmington - Mubarokah Mubarokah (PGRI Provinsi Jawa Timur, 2022)
This research was aimed to describe the types and the interpretation meanings of figurative languages found on Joe Biden’s Victory Speech in Wilmington. This research was conducted by using descriptive qualitative method. The subject of this research was the Joe Biden’s speech text in Wilmington. The researcher used two instruments namely: observation field note and table. The results showed There were 9 types of figurative language used in the speech delivered by Joe Biden. Based on the results findings as seen in the table above, those classification of figurative meaning are: metaphor containing 1 datum (1.81%), simile containing 9 data (16.36%), symbol containing 4 data (7.27%), personification containing 5 data (9.09%), synecdoche containing 7 data (12.73%), metonymy containing 5 data (9.09%), allegory containing 1 datum (1.81%), hyperbole containing 3 data (5.45%) and irony containing 20 data (36.36%). Based on the data examined, there were 55 data found on Biden’s speech consisting figurative language. Furthermore, the researcher describes the interpretation meanings of figurative language based on the data findings supported by Reaske (1996)’s theory and related theories about figurative language. There are 9 types of figurative language including: metaphor, simile, symbol, personification, synecdoche, metonymy, allegory, hyperbole and irony.